The Satan how God's executioner became the enemy - Stokes, Ryan E. (Grand Rapids, Michigan William B. Eerdmans Publishing Company, 2019)
The origin of the Satan -- The Satan and the innocent job -- Demons, evil spirits, fallen angels, and human sin -- The prince of Mastema and his deceptive spirits -- The prince of Mastema, enemy of God's people -- Demons, evil spirits, the Satan, and human responsibility for sin -- Belial, sin, and sectarianism -- Belial and the powers of darkness -- The Satan in the New Testament.
"The Satan: How God's Executioner Became the Enemy is a history of the origin, shaping, and reshaping of beliefs about (the) Satan. It traces the development of ideas pertaining to this figure from the earliest references to the Satan in the Hebrew Bible to the varied depictions of the Satan and his evil forces in the Jewish and Christian literature of the late Second Temple period. It explains the origin of this tradition as evidenced in the Hebrew Scriptures and describes the interpretive process that transformed an agent of God into the preeminent antagonist and archenemy of good"--
Includes bibliographical references and index
Keywords: Devil -- History of doctrines; Devil -- Biblical teaching